Challenges of managing HIV cytomegalovirus co-infection in the presence of pancytopenia - Vupmandla, Niveditha; Shivaswamy, Rajendra Prasad; BJ, Subhash Chandra; KC, Shashidhara (Indian Journal of Case Reports, 2024)
A 60-year-old male patient who presented with generalized weakness and low-grade fever was diagnosed to be human immunodeficiency virus (HIV) positive with a CD4 count of 17. Routine laboratory investigations revealed pancytopenia. Serum cytomegalovirus (CMV) DNA polymerase chain reaction (PCR) was positive and fundoscopy showed CMV retinitis in the right eye. The patient was started on tablet valganciclovir. After 2 weeks, the patient was brought back in an altered sensorium. He was found to have hyponatremia which was corrected. He was started on antiretroviral therapy and tablet valganciclovir was continued. The patient came back again after one and a half months with a urinary tract infection and fissure-in-ano. He was found to have severe neutropenia. Valganciclovir was stopped. He was started on injection granulocyte colony-stimulating factor. The patient clinically improved and his hematological parameters became normal. Patients having HIV and CMV co-infection with pre-existing pancytopenia have to be closely monitored as the medicines used for treatment can exacerbate the existing conditions.